Hepatic Hyaline Arteriolosclerosis in Patients with Chronic Hyperglycemia. (28th October 2021) - Kilpatrick, M; Lewin, D
Abstract: Introduction/Objective: Hyaline arteriolosclerosis is a common feature of diabetic microangiopathy. It results from hyperglycemia-induced endothelial cell dysfunction and can be found in many sites including the retina, kidney, and skin. This histologic finding is important because studies have shown that in the kidney it is an independent risk factor for cardiovascular complications. To our knowledge, an association between hyperglycemia and hyaline arteriolosclerosis in the liver has not be studied. We aimed to investigate whether chronic hyperglycemia is associated with this histologic finding in liver arterioles. Methods/Case Report: The first 50 liver biopsies performed at our institution starting January 1, 2020 were scanned into a digital pathology system (Philips, Cambridge, MA). For each biopsy, the patient's highest recorded hemoglobin A1c (HbA1c) up to one year from the date of biopsy was recorded. The biopsies were then grouped into two groups: those from patients with a HbA1c greater than 6.5%, and those with a HbA1c value less than 6.5 %. Next, the digested periodic acid Schiff (DPAS) intensity of the arteriolar vessels in each biopsy was graded 0 to 3 by a single pathology resident who was blinded to its corresponding HbA1c group. Grade 0 to 1 was considered negative staining. Grade 2 to 3 was considered positive staining and indicative of hyaline arteriolosclerosis. By the end of the data collection, each case had been given a staining category and a HbA1c group. A 2 x 2 contingency table was constructed. Results (if a Case Study enter NA): 37 of 50 patients had a recorded HbA1c meeting the study criteria. Of these 37 patients, 11 had an HbA1c greater than 6.5 % while 26 had an HbA1c less than 6.5%. Seven of the 11 biopsies from patients with an elevated HbA1c showed positive staining. Six of the 26 biopsies from patients with an HbA1c less than 6.5% showed positive staining. Conclusion: We hypothesized that patients living with hyperglycemia may be more likely to exhibit hepatic hyaline arteriolosclerosis. A chi-squared test of independence was performed to examine the association between a liver biopsy's HbA1c group and staining category. The relation between these variables was significant at p = < .05, χ 2 (2, N= 36) = 5.57, p = .0182, indicating liver biopsies with a HbA1c greater than 6.5 % are more likely to have this histologic finding. Future studies are needed to characterize diabetic hepatopathy, and its relatedness to macrovascular complications.